Introductory computational physics - Klein, Andi (Cambridge University Press, 2006)
Computers are one of the most important tools available to physicists, whether for calculating and displaying results, simulating experiments, or solving complex systems of equations. Introducing students to computational physics, this textbook, first published in 2006, shows how to use computers to solve mathematical problems in physics and teaches students about choosing different numerical approaches. It also introduces students to many of the programs and packages available. The book relies solely on free software: the operating system chosen is Linux, which comes with an excellent C++ compiler, and the graphical interface is the ROOT package available for free from CERN. This broad scope textbook is suitable for undergraduates starting on computational physics courses. It includes exercises and many examples of programs. Online resources at www.cambridge.org/0521828627 feature additional reference information, solutions, and updates on new techniques, software and hardware used in physics.